Development Of An Automatic Calculation Method For Ct Dose Estimation Based On Individual Specific Size In Paediatric Population - Abdulkadir, Muhammad Kabir (2022)
The current dose estimation based on CTDIvol in paediatric CT leads to significant inaccuracies in dose estimation due to inadequate size consideration. Size-specific dose estimate (SSDE) was employed to correct the effect resulting from the use of current CT protocols and minimise the radiation dose that been delivered more than double the intended dose to paediatric. This study aims to evaluate the current paediatric CT protocols and associated dose received by paediatric from CT scans. This study also aims to develop an automatic calculator using MATLAB algorithm for accurate patient size measurement and SSDE calculation. A retrospective survey was conducted to investigate CT protocols and associated dose (CTDIvol), patient size (manual measured Deff and Dw) and SSDE of paediatric patients undergoing head and abdomen CT scans. An automated calculation algorithm was developed on MATLAB platform for patient size measurement (Deff) and SSDE calculation. Numerical data analysed were scan parameters, estimated doses (CTDIvol and SSDE), manual and automated Deff estimates of patient size. Scan parameters and dose (CTDIvol) were compared with diagnostic reference ranges (DRLs) while automated SSDE calculator was validated with the manual size measurement and SSDE calculation. Local diagnostic reference ranges and patient size distribution were derived. The results showed a disparity of 7 to 51% between CTDIvol and SSDE. Automated calculator yields accurate measured size and calculated SSDE with an estimation error of less than 2%.